Description of the first marine interstitial ingolfiellid from Philippines, Ingolfiella alba sp. nov., with some remarks on the systematic of the genus (Amphipoda: Ingolfiellidae) - Iannilli, Valentina; Berera, Raffaella; Cottarelli, Vezio (Zootaxa, 2008)
The description of a new Ingolfiella of littoral interstitial water, the first finding among Ingolfiellidea for Philippines is presented. Male and female specimens are investigate and the new species seems close to the species group before included into the marine interstitial Tethydiella group. The new taxon shares a high number of features with I. xarifae Ruffo, 1966, described from Maldive Islands. The new species is characterized for the peculiar oosteogites morphology and for the presence in both sexes of spines and setae variously modified. Finally some data on species ecology and sampling sites are given.